Thermal stability of conductivity of composite comprising polyaniline and MCM-41 - Nur, Hadi; Abdul Rahman, Norizah; Endud, Salasiah; Lim, Kheng Wei (Plastics and Rubber Institute of Malaysia, 2007)

(untitled)
A composite of mesoporous silica (MCM-41) with a polyaniline (PANI) conducting polymer was synthesized by in situ polymerization method. PANI/MCM-41 conducting polymer composites were characterized by Fourier Transform Infrared (FTIR), UV-Vis, thermogravimetric analysis (TGA), Four-point probe for conductivity measurement and 13C CP/MAS NMR. It was revealed that although conductivity of PANI was reducedafter addition of MCM-41, from 1 to 10-1 S cm-1, its thermal stability of conductivity was significantly enhanced and demonstrated the desirability which efficacy of this polymermesoporous silica MCM-41 composite system in relatively high temperature applications (ca. 150 oC).